Simultaneous determination of inorganic ions in saline water from the Mekong Delta using ion chromatography - Quang Nhat Tran; Phuc Trong Phan; Huy Dang Nguyen; Nhi Ngoc Thi Vo; Han Gia Vu Le; Hai Son Truong-Lam (Water Science)
The economy of Vietnam is significantly influenced by agriculture, forestry, and fisheries; thus, developing analytical methods to assess water quality is crucial. Salinization is an escalating concern in the Mekong Delta, particularly in Ben Tre province, where it adversely affects the livelihoods and local economy. In saline water, besides NaCl, which is the predominant component, other ions such as K+, Ca2+, Mg2+, and SO42− are vital for crop development. This study introduces an ion chromatography technique with conductivity detection capable of simultaneously analyzing six ions in saline water samples with high precision. The standard curves demonstrated excellent linearity with a correlation coefficient (R2 >0.995) and commendable repeatability (%RSD <5%) for concentration ranges of 1–10 mg L−1 for cations, 0–10 mg L−1 for SO42−, and 10–50 mg L−1 for Cl−. The outcomes will be compared with those of reference methods, including Flame Atomic Absorption Spectrometry, Mohr Titration, and Turbidimetric Methods, revealing no significant differences in ion concentration determinations across six saline water backgrounds in Ben Tre province.